2018
DOI: 10.1038/s41598-018-30836-5
|View full text |Cite|
|
Sign up to set email alerts
|

PR-LncRNA signature regulates glioma cell activity through expression of SOX factors

Abstract: Long non-coding RNAs (LncRNAs) have emerged as a relevant class of genome regulators involved in a broad range of biological processes and with important roles in tumor initiation and malignant progression. We have previously identified a p53-regulated tumor suppressor signature of LncRNAs (PR-LncRNAs) in colorectal cancer. Our aim was to identify the expression and function of this signature in gliomas. We found that the expression of the four PR-LncRNAs tested was high in human low-grade glioma samples and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 39 publications
0
10
0
Order By: Relevance
“…Increasing studies have shown that lncRNAs play a crucial role in tumor progression [ 11 , 12 ]. Recently, molecular risk signatures as prognostic predictors of cancer progression were investigated, especially lncRNA signatures [ 13 , 14 ]. However, the prognostic value of ferroptosis-related lncRNAs signature in GC has not been systematically explored.…”
Section: Introductionmentioning
confidence: 99%
“…Increasing studies have shown that lncRNAs play a crucial role in tumor progression [ 11 , 12 ]. Recently, molecular risk signatures as prognostic predictors of cancer progression were investigated, especially lncRNA signatures [ 13 , 14 ]. However, the prognostic value of ferroptosis-related lncRNAs signature in GC has not been systematically explored.…”
Section: Introductionmentioning
confidence: 99%
“…LncRNAs regulate tumorigenesis and invasion by activating or silencing oncogenes via various mechanisms, such as epigenetic regulation, RNA decay and post‐translational modification 8 . Many lncRNAs have high levels of expression in brain tumours such as GBM and astrocytoma, and these lncRNAs have been shown to rely on various molecular mechanisms 9 …”
Section: Introductionmentioning
confidence: 99%
“…8 Many lncRNAs have high levels of expression in brain tumours such as GBM and astrocytoma, and these lncRNAs have been shown to rely on various molecular mechanisms. 9 In the current study, we identified a novel lncRNA, HOXA cluster antisense RNA 3 (HOXA-AS3). It was found to be one of the most up-regulated lncRNAs in GBM tissues.…”
mentioning
confidence: 95%
“…In vitro experiments of glioma tissues and cell lines revealed that PR-lncRNA expression was negatively correlated with SOX1, SOX2, and SOX9 stem cell factors. Knockdown of SOX abolished the role of PR-lncRNA silencing in glioma cell activity, indicating that the expression and function of PR-lncRNA were significantly altered in LGG formation ( Torres-Bayona et al, 2018 ). LncRNA H19 can enhance tumorigenesis by directly inducing the c-Myc oncogene ( Barsyte-Lovejoy et al, 2006 ).…”
Section: Long Non-coding Rnas Implications In Various Brain Tumorsmentioning
confidence: 99%